Neurodevelopmental and visual outcomes of infants at risk of neurodevelopmental disability following dietary supplementation in infancy - Andrew, M (2016)
Neurodevelopmental and visual outcomes of infants at risk of neurodevelopmental disability following dietary supplementation in infancy Morag Jane Andrew, Wolfson College, Michaelmas 2016 Abstract Background: Docosahexaenoic acid (DHA), choline and uridine-5-monophosphate (UMP) are important brain nutrients which form phosphatidylcholine, the most abundant brain membrane phospholipid. DHA, choline and UMP supplementation increases rodent brain phospholipids, synaptic components, functional brain connectivity and cognitive performance. This novel pilot study supplemented infants at risk of neurological impairment (ARNI) with a nutrient combination containing these neurotrophic compounds. Aims: 1) In a double blind randomised control trial (RCT), investigate if intake of a specific nutrient combination improves neurodevelopmental and visual outcome in infants ARNI. 2) Using novel measures of cortical visual function, investigate the effect of perinatal brain injury severity, gestational age at birth and sex upon visuocognitive development in infants at risk of neurodevelopmental impairment. Method: Recruitment was from UK neonatal units. Eligibility: ≤31 weeks, weight <9th percentile; <31 weeks with ≥ Grade II intraventricular haemorrhage (IVH) or preterm white matter injury (PWMI); 31-40 weeks with ≥ Grade II IVH or PWMI, ≥ Sarnat Grade II HIE or defined brain MRI abnormalities. Stratification was by sex, gestation and brain injury severity. Randomised infants received neurotrophic supplementation or placebo, for 2 years. Primary outcome was Bayley Scales of Infant Development III (BSID III) composite cognitive score (CCS) after 2 years. Secondary outcomes included BSID III composite language score (CLS) and BSID III composite motor score (CMS). Cortical visual measures were pattern reversal visual event related potential (PR-VERP) latency (transient and calculated), orientation reversal visual event related potentials (OR-VERP), and the Fixation Shift test (FS). Functional behavioural vision was assessed using the Atkinson Battery of Child Development for Examining Functional Vision (ABCDEFV). Local Ethics Committee approval was granted. Results: 62 neonates were recruited. After 2 years, mean CCS in the intervention group was 87.7 (SD 20.4) and 81.6 (SD 18.5) in the placebo group (mean difference = 2.28, p=0.13; -0.2, 18.2). Mean CLS in the intervention group was 91.5 (SD 20.1) and 83.2 (SD 19.6) in the placebo group (mean difference = 2.74, p=0.1; -2.4, 18.3). CMS was similar in both groups. In relation to trial visual outcome measures, more infants in the placebo group gave a statistically significant OR-VERP response than in the intervention group (p=0.03). There were no statistically significant differences between the placebo and intervention on any other trial visual outcome measure. Cohort analyses indicate that transient PR-VERP latency is prolonged in children at risk of neurodevelopmental disability compared to typically developing infants (mean difference = -23.3, p=0.015, 95% CI -42.10 - -4.54). Calculated PR-VERP latency is prolonged to an even greater extent in children at risk of neurodevelopmental disability compared to typically developing infants (mean difference -148.6, p=0.000, 95% CI -179.7- -117.43), and remains prolonged across the age range tested. Conclusions: 1) The difference in CCS and CLS between intervention and placebo groups represents a clinically significant effect size. Use of neurotrophic micronutrient supplementation in infants ARNI warrants exploration in a large multicentre RCT. 2) Calculated PR-VERP latency may be a more appropriate outcome measure of cortical visual function than transient PR-VERP latency in infants at risk of neurodevelopmental disability.